Pengaruh Independensi Dan Keahlian Profesi Terhadap Kinerja Badan Pengawas Lembaga Perkreditan Desa (LPD) Di Kecamatan Banjarangkan - Pradita, I Komang Dede; Kusumawati, Ni Putu; Pramuki, Ni Made Wisni Arie (UNHI Press, 2025)
Thisiresearch aims to determine the influence of independence and professional expertise on thevperformance of supervisory bodies atiVillageiCredit Institutionsl(LPD)oin Banjarangkan District. The population in thisfstudy was the entire supervisory body of the 28 LPDs still operating in Banjarangkan tDistrict, totaling 73 peoples. The number of samples in this study was 73 peoples cwho were determinedg using a saturated nsampling technique and tested using the Partial Least Squares analysis technique. The results of this research show that independenceuhas a positive effecthon thebperformance ofhthe LPD supervisory body in Bajarangkan District. Professional expertise hasga positiven influence onnthe performance of the LPDksupervisory body ini Bajarangkan lDistrict. For all LPDksupervisors inh Bajarangkan kDistrict, thejresults ofkthis research cani bei used asjconsiderationi in designingc regulations and policies relatedv to improving performance.